Topical ozone application for severe acne with serological evidence of prior varicella-zoster infection after unsuccessful antibiotic and corticosteroid treatment: a case report - Taras Pyatkovskyy; Olena Pokryshko; Artur Markowski; Tetiana Chernyshova; Serhii Danylkov (Journal of Medical Case Reports)
Abstract Background Acne fulminans is a rare and extreme form of inflammatory acne, which is characterized by the sudden onset of painful, ulcerative nodules and systemic symptoms such as fever, malaise, arthralgia, leukocytosis, and potential scarring. Case presentation We present the case of a 16-year-old white European (Polish) female patient with acne vulgaris that progressively worsened despite treatment with oral isotretinoin, estrogens, topical antibiotics, and corticosteroids. She subsequently developed systemic complications, including fever, malaise, severe musculoskeletal pain, and tachycardia, and was hospitalized, where she received corticosteroids, antibiotics, and isotretinoin; however, the inflammatory and purulent processes persisted. Following discharge, her condition further deteriorated, presenting as severe swelling, pustules, and inflammatory lesions. Upon consulting a different clinic, all previous medications were discontinued, and a treatment regimen involving topical ozone was initiated. This included washing with ozonated water (2.4 ppm) and applying ozonated olive oil (peroxide index 2300) twice daily. The therapy resulted in a rapid reduction of inflammation and purulent lesions, with significant improvement observed within days. Conclusion This case report suggests a potential benefit of combining ozonated water and ozonated oil as a novel therapeutic approach for refractory acne fulminans.